2011
DOI: 10.1590/s1516-80342011000400011
|View full text |Cite
|
Sign up to set email alerts
|

Média dos valores da frase em crianças com desvio fonológico evolutivo

Abstract: Purpose: To determine the average values of phrase in children with phonological disorder, and to compare it with benchmark values proposed in literature. Methods: The sample consisted of 16 children with phonological disorders, seven females and nine males, with ages between 4 years and 5 months and 7 years and 7 months. After confirmation of the diagnosis of developmental phonological disorder, subjects were submitted to language assessment through the investigation of the average values of phrase, as propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…These findings are in agreement with previous studies (24,30) which identify the age of 5 as a significant milestone in phoneme acquisition, and consequently, in the suppression of phonological processes.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in agreement with previous studies (24,30) which identify the age of 5 as a significant milestone in phoneme acquisition, and consequently, in the suppression of phonological processes.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies concluded that language deficits are related to phonological disorders [18], compensatory articulation [19], parent interaction, and stimulation [20]. Thus, speech and language pathologists should evaluate speech and language development in children with cra-…”
Section: Discussionmentioning
confidence: 99%
“…Based on that point of view, several children with PD seem to have difficulties in other language areas, such as syntax, morphology and lexical. In some cases, the PD prevents the development of those areas 1,8 . So, according to literature, pragmatic, semantic, morph-syntactic and phonological aspects should not be separated, because they are related in the development of linguistic skills 8,9 .…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, the PD prevents the development of those areas 1,8 . So, according to literature, pragmatic, semantic, morph-syntactic and phonological aspects should not be separated, because they are related in the development of linguistic skills 8,9 . The severity of the PD may be determined after several classifications.…”
Section: Methodsmentioning
confidence: 99%